Romheld’s Gastrocardiac Syndrome, diagnosing a complex of cardiologic and gastroenterologic symptoms - Bijata, Bartosz; Burek, Dawid; Paszkowska, Aleksandra; Kujawa, Aleksandra; Matuszewska, Urszula; Nykowska, Aleksandra; Beutler, Katarzyna (Journal of Education, Health and Sport, 2024)
In clinical practice among cardiac patients, symptoms of palpitations diagnosed as premature beats or episodes of atrial fibrillation (AF) are very frequently reported. One of the most common diseases in the field of gastroenterology is gastroesophageal reflux disease (GERD) . However, it may happen that the coincidence of the above-mentioned disease entities may predispose to the development of arrhythmias. In this article we describe the case of a 65-year-old man, without previously diagnosed diseases, in whom a clear association of arrhythmias with gastrointestinal complaints was observed. The presence of a burning sensation in the lower sternal region and typical symptoms resulting from esophagitis aggravated by triggers allows us to suspect esophageal reflux disease. Diagnostic tests performed for concomitant cardiac diseases did not reveal an organic cause of the arrhythmia. The recurrent course of symptoms observed in the present case and the analysis of the cause-effect course made us to diagnose gastrointestinal syndrome, also referred to as Romheld’s Syndrome.